Efficacy of Liquid Nitrogen versus Trichloroacetic Acid 40% in Treatment of Solar Lentigo - رومية عبد الحليم; صبوح وفيق; يوسف لميس (Latakia University Journal -Medical Sciences Series, 2021)
Background and objective: solar lentigo is one of the most common benign pigmented lesions caused by chronic exposure to the sun. With major cosmetic concern, many treatments are suggested but none of them is considered to be the most effective with less side effects. However, liquid nitrogen and trichloroacetic acid are cost-effective alternatives in the treatment of solar lentigo. Our study is to compare between those two alternatives to determine which is the most effective with less side effects depending on the Fitzpatrick’s skin type. Patients and methods: 34 participants with solar lentigines on the back of the hands (4 type II, 19 type III, and 11 type IV), underwent to two treatment sessions with liquid nitrogen and trichloroacetic acid 40% for each hand, at 4 week intervals. The results demonstrated that liquid nitrogen was more likely to produce significant lightening than trichloroacetic acid 40% (p-value = 0.01), but was more painful and needed longer time to heal. Although liquid nitrogen had better results in higher Fitzpatrick’s skin types (type IV) than trichloroacetic acid 40%, it also caused hypopigmentation which makes Trichloroacetic acid 40% a better choice for those patients. Conclusion: liquid nitrogen is more effective choice to treat solar lentigo comparing to trichloroacetic acid 40%, but as for dark skinned patients it’s better to use trichloroacetic acid 40% to avoid hypopigmentation.